Wirklichkeitsbrüche. Theorie und Analyse mit Blick auf Texte der frühen Moderne und Postmoderne - Brössel, Staphan (Studia Germanica Posnaniensia, 2013)
The article concentrates on the collision between plural concepts of reality in narrative fiction. For that purpose it focuses on theoretical aspects of world construction as well as on issues concerning the notions of character and narrative instances from a narratological point of view. Narrative collisions depend on heterogeneous, pluriregional or instable worlds, characters’ deficits in knowledge and problematic perception, metalepses and the exposure and handling of the borderline between two or more concepts of reality. To illustrate these theoretical preliminaries the article attempts to show how texts functionalise such structures to create narrations of transition. Arnold Höllriegel’s The Films by Princess Fantoche (1913) was written in the context of the early modern period. It correlates the collision of ‘realities’ to general questions of the modern crisis about whether to follow traditional ways or to find new ones. In Benjamin Stein’s Replay (2012) subjectivity is raised as a problem insofar as the narrating character loses himself in entangled time-circles and delivers an unreliable narration. Stein discusses the postmodern game of intertextuality, technologism, eroticism, and self-reflection as well as the loss of the narrative and the wish for its renewal.